Deciphering the Molecular Mechanisms of Cancer: Role of Proto-Oncogenes and Targeted Therapies - S. Hari Hara Sudhan, (Asian Journal of Pharmaceutics (AJP), 2025)
Cancer is a multifaceted disease characterized by uncontrolled cell growth, invasion, and metastasis. At the molecular level, proto-oncogenes play a critical role in normal cell growth and differentiation. However, their conversion into oncogenes due to mutations or overexpression can drive tumorigenesis. This review delves into the molecular transformation of proto-oncogenes into oncogenes and the underlying causes, including genetic mutations, chromosomal abnormalities, and viral infections. In addition, we explore the significance of tumor suppressor genes in counteracting oncogenic signals and their role in maintaining cellular integrity. Advancements in cancer research have led to the development of targeted therapies that specifically inhibit oncogene-driven malignancies. Initially, oncogene-targeted drugs such as Herceptin, gefitinib, and STI-571, along with monoclonal antibodies, have revolutionized cancer treatment by disrupting tumor-promoting pathways while minimizing damage to normal cells. Furthermore, recent developments in oncogene-directed therapies are paving the way for precision medicine in oncology. By understanding the molecular basis of cancer, researchers can develop innovative therapeutic strategies to combat malignancies at their roots. This review highlights the importance of proto-oncogene regulation, oncogene inhibition, and emerging targeted therapies in the fight against cancer, offering insights into future directions in molecular oncology.